Can neck circumference predict insulin resistance in older people? A cross-sectional study at primary care in Brazil - Maria Auxiliadora Nogueira Saad; Maria Luiza Garcia Rosa; Giovanna Balarini Lima; Rubens Antunes da Cruz Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: This study focused on the correlation between neck circumference and other anthropometric measurements and cardiovascular risk factors and insulin resistance in the elderly in Niterói, Rio de Janeiro State, Brazil. This was a cross-sectional study in 411 patients seen in primary care. Anthropometric measurements including neck circumference, body mass index (BMI), waist circumference (WC), and waist-hip ratio (WHR) were recorded. Bioelectrical impedance analysis (BIA) estimated the percentage of total body fat (%TBF). Insulin resistance was estimated by HOMA-IR (homeostasis model assessment IR index). The data were analyzed by the Mann-Whitney test and the correlation between numerical variables by Spearman's test. Receiver operating characteristic (ROC) was used to assess the anthropometric measurements' predictive capacity to diagnosis insulin resistance. Neck circumference was positively correlated with WC, BMI, WHR, %TBF, and HOMA-IR in both sexes. In women, neck circumference showed higher AUC (area under the curve) for insulin resistance. In men, WC showed higher AUC, followed by BMI and neck circumference. The current study in Southeast Brazil suggests that neck circumference can predict insulin resistance, an important marker of cardiovascular risk in the elderly population treated in primary care.